Portable potable water treatment system - Mangena, Lebogang Vuyo (My University, 2019)
Safe access to safe drinking water is an issue is many developing countries where water treatment service providers are not able to effectively treat water sources impacted by sewage and other pollutants. This research focuses on the quality of urban river water, as well as on the design and use of a small-scale water treatment technology that is aimed at assisting communities lacking access to safe drinking water. The Portable Potable Water Treatment System (PPWTS) is a small-scale system made up of three chambers, namely a constructed wetland (CW), a chamber containing charcoal and a UV chamber utilising UV LEDs for disinfection. River water from the Fairlands Spruit River was passed through the system in an attempt to treat the water to the potable water standards set by the World Health Organization (WHO) and the South African National Standards. The average pH, E.C., turbidity, phosphate, nitrate, sulfate, COD, TOC, total coliform, E. coli, aluminium, lead and manganese values obtained through analysis and testing of the feed water were 8.40, 292 μS/cm, 3.27 NTU, 0.052 mg/L, 2.93 mg/L, 27.8 mg/L, 19.5 mg/L, 6.71 mg/L, 56800 MPN/100 mL, 22900 MPN/100 mL, 55.8 μg/L, 2.7 μg/L and 24.91 μg/L respectively. The results obtained through using the PPWTS to treat river water revealed an increase in the average pH of river water to 8.77, a 28.53% increase in E.C., a 36.09% decrease in turbidity, a 92.31% increase of phosphates, a 55.63% removal of nitrates, a 23.51% removal of COD, a decrease in TOC of 16.10%, a total coliform removal rate of 64.86%, a decrease in E. coli bacteria of 91.94% and a 34.96% decrease in sulfates. The removal rates for aluminium, lead and manganese achieved using the PPWTS were 47.69%, 10% and 48.37% respectively. Though substantial removal of total coliforms and E. coli was achieved, the water collected from the outlet of the PPWTS did not meet the SANS and WHO drinking water standard of 0 MPN/100 mL for total coliforms and E. coli. The design of the system could do away with the UV chamber as it is was not effective in removing total coliforms and E. coli bacteria.
Keywords: Water quality management; Water--Purification--South Africa; Water treatment plants.; Water treatment plants.